Identifying Dermatological Emergencies in Out-Patient Care: When to be Worried (Canadian Allergy & Immunology Today, 2022)
Dermatological emergencies require early identification and must be addressed immediately. According to a study from 2005, dermatological concerns constitute 15-20% of visits to family physicians and emergency departments. Understandably, different cutaneous manifestations may be challenging to categorize as the presentation of various lesions may overlap with respect to the diagnosis. It is essential for physicians providing outpatient care to consider that although lesions may only appear to be manifesting on the skin, systemic involvement may be a factor or may follow depending on the pathology of the underlying illness. As physicians seeing patients in outpatient care settings may be the first point of contact for patients, familiarity with the identification of specific lesions, the timeline of their occurrence, signs and symptoms at presentation, and their causes are valuable information needed to determine the urgency of their patients’ situation. This article identifies some common lesions of concern that may require closer attention and some of the dermatological emergencies associated with these lesions.